2014
DOI: 10.14402/jkamprs.2014.36.6.266
|View full text |Cite
|
Sign up to set email alerts
|

The Retrospective Study of Closed Reduction of Nasal Bone Fracture

Abstract: Purpose:This study was conducted in order to investigate the therapeutic effect of closed reduction according to a classification in patients with nasal bone fracture.Methods:The study was conducted retrospectively on 186 patients with a mean age of 38 years (range: 7 to 80 years). All patients were diagnosed by clinical and radiologic examination, and then classified according to Hwang’s classification by computed tomography. The patients were further classified by their age, gender, causes of fracture, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
(21 reference statements)
4
17
0
3
Order By: Relevance
“…This study represents one of the largest retrospective reviews on nasal bone fracture and closed nasal reduction outcomes, especially within the United States at a regional level 1 trauma center. 2,6,19,26 Other studies have similarly found assault to be the most common etiology of nasal bone fracture, especially in urban populations. 27,28 Of the patients who underwent CT evaluation, associated facial fractures tended to be in the midface region.…”
Section: Epidemiologymentioning
confidence: 92%
“…This study represents one of the largest retrospective reviews on nasal bone fracture and closed nasal reduction outcomes, especially within the United States at a regional level 1 trauma center. 2,6,19,26 Other studies have similarly found assault to be the most common etiology of nasal bone fracture, especially in urban populations. 27,28 Of the patients who underwent CT evaluation, associated facial fractures tended to be in the midface region.…”
Section: Epidemiologymentioning
confidence: 92%
“…Another study reported that the most common complication was postoperative pain. 18 Many patient satisfaction surveys have reported that 70 to 80% of the patients were satisfied; 1,4,26-29 however, satisfaction tended to be low in severe cases with nasal septum fracture. 28 Hwang et al 15 reported that it should be explained to the patient that nasal deformity and deviation and obstruction of the nasal septum are postoperatively observed in 10% of the cases of nasal bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that the coexisting facial bone fractures other than nasal septum fractures range from 5 to 15.7%; 1,4,5,15,17 blow-out fractures were most frequent, followed by cheekbone and maxillary bone fractures. 4,5,18 It appears that this is because the orbital wall and the cheekbone/maxilla are anatomically adjacent to the nasal bone. 5 Among our cases, 11.7% cases involved coexisting facial bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Han-Kyul Park, Jae-Yeol Lee et al, patients in their 20s accounted for the highest proportion, and those in their 40s to 50s accounted for the second highest proportion. [5].…”
Section: Ct Scan Axial View Showing Depressed Fracture Of Nasal Bonementioning
confidence: 99%